Bortezomib promotes the TRAIL-mediated killing of resistant rhabdomyosarcoma by ErbB2/Her2-targeted CAR-NK-92 cells via DR5 upregulation - Catrin Heim; Leonie Hartig; Nadine Weinelt; Laura M. Moser; Emilia Salzmann-Manrique; Michael Merker; Winfried S. Wels; Torsten Tonn; Peter Bader; Jan-Henning Klusmann; Sjoerd J.L. van Wijk; Eva Rettinger (Molecular Therapy: Oncology)
Treatment resistance and immune escape are hallmarks of metastatic rhabdomyosarcoma (RMS), underscoring the urgent medical need for therapeutic agents against this disease entity as a key challenge in pediatric oncology. Chimeric antigen receptor (CAR)-based immunotherapies, such as the ErbB2 (Her2)-CAR-engineered natural killer (NK) cell line NK-92/5.28.z, provide antitumor cytotoxicity primarily through CAR-mediated cytotoxic granule release and thereafter—even in cases with low surface antigen expression or tumor escape—by triggering intrinsic NK cell-mediated apoptosis induction via additional ligand/receptors. In this study, we showed that bortezomib increased susceptibility toward apoptosis in clinically relevant RMS cell lines RH30 and RH41, and patient-derived RMS tumor organoid RMS335, by upregulation of the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor DR5 in these metastatic, relapsed/refractory (r/r) RMS tumors. Subsequent administration of NK-92/5.28.z cells significantly enhanced antitumor activity in vitro. Applying recombinant TRAIL instead of NK-92/5.28.z cells confirmed that the synergistic antitumor effects of the combination treatment were mediated via TRAIL. Western blot analyses indicated that the combination treatment with bortezomib and NK-92/5.28.z cells increased apoptosis by interacting with the nuclear factor κB, JNK, and caspase pathways. Overall, bortezomib pretreatment can sensitize r/r RMS tumors to CAR- and, by upregulating DR5, TRAIL-mediated cytotoxicity of NK-92/5.28.z cells.